Analysis of Islamic Law on the Efforts of Covering Physical Evidence of Murabahah Financing Transactions - Ubaid Aisyul Hana; Muhammad Syarifudin (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2021)
The research aims to answer the problem of how to cover physical evidence by PT. BPRS Jabal Nur according to Islamic legal analysis. The research data is collected through interviews and the documentation is then analyzed using descriptive analysis techniques, namely the most basic analysis to describe the data in general. The results of the study concluded that the policies agreed upon by the BPRS Jabal Nur Surabaya were expressly prohibited by Islamic law, because they did not comply with the regulations made by the government. As explained in the Koran Surat al-Nisa’ verse 59. The policy is the covering (manipulation) of physical evidence in the form of notes for customers who do not deposit notes for certain reasons. It was done by the bank due to a lack of staff in handling the above problems and a lack of customer knowledge about the importance of these notes for the bank in their annual reports. In line with these conclusions, BPRS Jabal Nur must be firm with customers to submit physical evidence in the form of notes and tighten the recruitment process for the company so that it is better than what is expected by BPRS Jabal Nur Surabaya.